2012
DOI: 10.1377/hlthaff.2010.0965
|View full text |Cite
|
Sign up to set email alerts
|

Overprescribing In China, Driven By Financial Incentives, Results In Very High Use Of Antibiotics, Injections, And Corticosteroids

Abstract: In appropriate prescribing is a global problem. It is especially salient in China, where drug sales constitute a major portion of health care providers' incomes, price distortions are rampant, and oversight is lax. However, few data exist on the prevalence of inappropriate prescribing in China. This study, the first of its kind in China, examined 230,800 prescriptions written between 2007 and 2009 by 784 community health institutions in 28 cities across China. The data show substantial overprescribing, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(202 citation statements)
references
References 6 publications
2
196
0
Order By: Relevance
“…In China, antibiotics misuse is pervasive [6,7], leading to very high and growing rates of AMR in both hospital and community-acquired infections [810]. A review of antibiotic use in China demonstrated that 80% of inpatients and 50.3% of outpatients were prescribed with antibiotics, and as many as 75% of patients with seasonal influenza were treated with antibiotics [11].…”
Section: Introductionmentioning
confidence: 99%
“…In China, antibiotics misuse is pervasive [6,7], leading to very high and growing rates of AMR in both hospital and community-acquired infections [810]. A review of antibiotic use in China demonstrated that 80% of inpatients and 50.3% of outpatients were prescribed with antibiotics, and as many as 75% of patients with seasonal influenza were treated with antibiotics [11].…”
Section: Introductionmentioning
confidence: 99%
“…12 In China, antibiotics are substantially overprescribed as drug sales revenue constitutes a major proportion of healthcare providers' incomes. 63 In response to increasing AMR, China's first explicit attempt to rationalize antibiotic use came in the shape of national hospital guidelines (2004) 64 and a concurrently launched containment policy, which sought to ban the sale of antibiotics to patients without prescription. 65 The effectiveness of these policy measures was not systematically evaluated, and weak enforcement is likely to have limited their impact.…”
Section: Responsible Use Through Structural Reform and Strengthened Hmentioning
confidence: 99%
“…63 In 2007, an estimated 90,000 tons of antibiotics were used in humans. 73 The Ministry of Health (MoH) set up the National Healthcare Associated Infection Surveillance System (NHAISS) in 2001 to monitor antibiotic usage in hospitals, 74 and the MoH National Antibacterial Resistance Investigation Net (Mohnarin) in 2004 to detect and monitor antibiotic resistance.…”
Section: Case Study 2: Antibiotic Prescription In China: Systemic Andmentioning
confidence: 99%
“…generic statins accounted for only 9% to 10 % of total statins in recent years in hospitals in China international context (175). The low use of generics is exacerbated by the need for hospitals to make money from drug procurement for their sustainability and physicians to supplement their income, with this incentive system also stimulating overuse of injections (174,(176)(177)(178) Box 2 -Potential requirements to successfully implement a generic substitution policy (adapted from (118)).…”
Section: Ukincluding Scotlandmentioning
confidence: 99%